2019
DOI: 10.3390/agronomy9070360
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Water and Fertilizer on Yield, Soil Water and Nitrate Dynamics of Young Apple Tree in Semiarid Region of Northwest China

Abstract: Exploring the interactive effect of water and fertilizer on yield, soil water and nitrate dynamics of young apple tree is of great importance to improve the management of irrigation and fertilization in the apple-growing region of semiarid northwest China. A two-year pot experiment was conducted in a mobile rainproof shelter of the water-saving irrigation experimental station in Northwest A&F University, and the investigation evaluated the response of soil water and fertilizer migration, crop water product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Studies concluded that drip irrigation with irrigation quota less than 300 mm can obtain higher WUE but the low crop yield, while excessive drip irrigation has no obvious effect on increasing yield (Liu et al 2011a). In this study, compared with T1 treatment, the WUE and NUE for T2 treatment were significantly improved, but the yield only decreased by 1.21%, which was similar to the research of Zhou et al (2019), who found that the soil moisture lower limit of 65%-75% FC result in the yield decreased by 7.5% while the IWUE increased by 11.2% when compared with the soil moisture lower limit of 75%-85% FC.…”
Section: Crop Growth Yield Water and Nitrogen Use Efficiency With Soi...supporting
confidence: 89%
“…Studies concluded that drip irrigation with irrigation quota less than 300 mm can obtain higher WUE but the low crop yield, while excessive drip irrigation has no obvious effect on increasing yield (Liu et al 2011a). In this study, compared with T1 treatment, the WUE and NUE for T2 treatment were significantly improved, but the yield only decreased by 1.21%, which was similar to the research of Zhou et al (2019), who found that the soil moisture lower limit of 65%-75% FC result in the yield decreased by 7.5% while the IWUE increased by 11.2% when compared with the soil moisture lower limit of 75%-85% FC.…”
Section: Crop Growth Yield Water and Nitrogen Use Efficiency With Soi...supporting
confidence: 89%
“…Some agronomic indicators, including agronomic efficiency (AE) and partial factor productivity (PFP), were often used to describe fertilizer use efficiency [24,25]. There have been numerous studies on nutrient use efficiency [26][27][28][29]. The agronomic efficiency of fertilizer N, P, and K (AE-N, AE-P and AE-K) were the yield increase per unit of fertilizer N, P, and K applied.…”
Section: Introductionmentioning
confidence: 99%
“…Low irrigation was not conducive to effectiveness of fertilizers, and WUE was at its minimum [7]. Zhou et al found that for mature apples, controlling soil moisture to 65%-75% of field capacity and nitrogen application to 20 g/tree was the best combination of water and fertilizer conservation [8].…”
Section: Introductionmentioning
confidence: 99%